MENGAPA PEMBIAYAAN BERBASIS BAGI HASIL RENDAH DI PERBANKAN SYARIAH? (SUATU KAJIAN MENGGUNAKAN PENDEKATAN GROUNDED THEORY) - Sabrina Sabrina; M.Shabri Abd. Majid (FEB Universitas Syiah Kuala, 2019)
The purpose of this study is to identify factors influencing the low volume of profit sharing-based financing products of Bank Aceh Syariah. This study uses a grounded theory approach through interviews with several related parties, including: the academician, practitioners, customers, and regulators. The problem of low profit sharing-based financing products in this study is viewed from three aspects: internal, external, and regulation aspects. Based on the results of the study, from the internal aspect of bank, the problem of profit sharing-based financing productst is caused by six factors, namely: High risk, Lack of quality and quantity of Human Resources, Complicated handling, No product innovation, Asymmatric information, and Lack of socialization. Meanwhile, the external aspects of the bank (customer) is caused by three factors, namely: Moral hazard, Lack of community’s knowledge on Islamic banking products, and Low of demand. Finally, from the aspect of the regulation, the low profit sharing-based financing products caused by lack of support from the regulator. Based on the results of this study, the bank is expected to develop and innovate its products in order to minimize the risk, as well as to socialize to the community so that people know the products of Islamic banking. To the customers of the Islamic banking are expected to better understand products of the Islamic Banks. The Regulators are expected to regulate supporting policies to encourage the growth of profit sharing-based financing products so that the Islamic Bank would enhance the economic welfare of the Islamic society in the future.Keywords: Profit Sharing Financing, Bank Aceh, Factors, Internal Bank, External bank, Regulation.AbstrakTujuan dari penelitian ini adalah untuk mengidentifikasi faktor-faktor yang mempengaruhi rendahnya volume produk pembiayaan berbasis bagi hasil di PT Bank Aceh Syariah. Penelitian ini menggunakan pendekatan grounded theory melalui wawancara dengan beberapa pihak terkait, termasuk: Akademisi, Praktisi, Pelanggan, dan Regulator. Masalah produk pembiayaan berbasis pembagian keuntungan rendah dalam penelitian ini dilihat dari tiga aspek: Aspek Internal, Eksternal, dan Peraturan. Berdasarkan hasil penelitian, dari aspek internal bank, masalah produk pembiayaan berbasis bagi hasil disebabkan oleh enam faktor, yaitu: Risiko tinggi, Kurangnya kualitas dan kuantitas Sumber Daya Manusia, Penanganan yang rumit, Tidak ada inovasi produk , Informasi asimmatrik, dan Kurangnya sosialisasi. Sementara itu, aspek eksternal bank (pelanggan) disebabkan oleh tiga faktor, yaitu: Bahaya moral, Kurangnya pengetahuan masyarakat tentang produk perbankan syariah, dan Rendahnya permintaan. Akhirnya, dari aspek regulasi, rendahnya produk pembiayaan berbasis bagi hasil disebabkan oleh kurangnya dukungan dari regulator. Berdasarkan hasil penelitian ini, bank diharapkan mengembangkan dan berinovasi produk-produknya untuk meminimalkan risiko, serta untuk bersosialisasi kepada masyarakat sehingga masyarakat mengetahui produk-produk perbankan syariah. Bagi para pelanggan perbankan syariah diharapkan untuk lebih memahami produk-produk Bank Syariah. Para regulator diharapkan untuk mengatur kebijakan pendukung untuk mendorong pertumbuhan produk pembiayaan berbasis bagi hasil sehingga Bank Islam akan meningkatkan kesejahteraan ekonomi masyarakat Islam di masa depan.